Effects of COVID-19 vaccine type on Guillain-Barré syndrome: Two cases and a literature review - Hsin-Yu Lee; Wan-Ching Lien (Taylor & Francis Group, 2023)
Guillain-Barré syndrome (GBS) is a rare but severe complication of COVID-19 vaccination. We report two cases of GBS following vaccination with the adenovirus vector vaccine ChAdOx1 nCoV-19 (Vaxzevria, AstraZeneca) and review the relevant literature. Relevant studies published between December 2020 and May 2022 including 881 patients with GBS were reviewed. GBS incidence and the need for mechanical ventilation were reported at a higher level among patients receiving Vaxzevria (n = 400). However, incidence cannot be accurately estimated from case reports. Thus, the true GBS rates following COVID-19 vaccination should be determined by population-based data.